Being Reminiscent of War Memories: A Study of Identity and Love in Easterine Kire’s Mari (International Journal of Food and Nutritional Sciences, 2022)
Easterine Kire is one of the prominent writers from Nagaland, India. She focuses on the indigenous identity of the Naga Angami people in her writings. Kire is the first Naga novelist to write in English so as to givevoice to Naga people. The novel Mari was published in 2010.She uses her personal history in her historical novel, Mari in order to rebuild and represent the unforgettable Battle of Kohima. The war was fought from 4th April to 22nd June 1944. The story revolves around the central character Mari, the protagonist. Kire reveals the bitter experiences of Mari, along with the nativesin the war-afflicted region during World War II when the Japanese invaded Kohima. As Kire recollects the past Nagaland, she clearly describes the prewar and post-war condition of Kohima. She uses the personal memory of her aunt. This paper examines how Kire in the novel Marichallenges the concept of history as a grand narrative foregrounding the subjective narrative of Mari in the context of the Battle of Kohima. This paper also highlights how Mari’s self and identity as well as the collective identity of the Naga people are affected by the onslaught of war. The war leaves a scar on the personal memory of Mari and the collective memory of Naga people.